2020
DOI: 10.3390/w12041129
|View full text |Cite
|
Sign up to set email alerts
|

Sea Level Rise Effect on Groundwater Rise and Stormwater Retention Pond Reliability

Abstract: The coastal areas of Florida, United States, are exposed to increasing risk of flooding due to sea level rise as well as severe hurricanes. Florida regulations suggest constructing stormwater retention ponds as an option to retain excess runoff generated by the increased impervious area and to protect the environment by reducing pollutants from new developments. Groundwater level rise can significantly lower the soil storage capacity and infiltration at retention ponds, in turn, reducing the pond's capacity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…These tide gates reduce tidal inundation (Sadler et al., 2020; Shen et al., 2019), including efforts to make these tide gates responsive to current and predicted inundation to increase their efficacy (Sadler et al., 2020). Though this retrofit to the current stormwater network may be effective in the short‐to medium‐term, predicted increases in sea level and groundwater will inevitably lead to continuously inundated outfalls in vulnerable locations and decreased surface storage of stormwater further inland (Davtalab et al., 2020; Rotzoll & Fletcher, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These tide gates reduce tidal inundation (Sadler et al., 2020; Shen et al., 2019), including efforts to make these tide gates responsive to current and predicted inundation to increase their efficacy (Sadler et al., 2020). Though this retrofit to the current stormwater network may be effective in the short‐to medium‐term, predicted increases in sea level and groundwater will inevitably lead to continuously inundated outfalls in vulnerable locations and decreased surface storage of stormwater further inland (Davtalab et al., 2020; Rotzoll & Fletcher, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…While groundwater interactions with the retention ponds in Norfolk have not been studied specifically, it has been demonstrated that increased groundwater table levels due to sea level rise could contribute to retention ponds in coastal areas, decreasing their ability to appropriately manage consecutive storm events. 39 To address this need, groundwater exchange with controlled ponds is simulated in a number of the scenarios in this research.…”
Section: Swmm Modelmentioning
confidence: 99%
“…The land area that is less than 10 m above sea level is just 2 % of the world's total land area, yet it is home to 10 % of the world's population and 13 % of the world's urban population (McGranahan et al, 2007). SLR, extreme sea level events, and land subsidence have the potential to significantly affect landscapes, land use, infrastructure, morphology and ecosystem services, therefore coastal areas are among the most vulnerable regions in the world (Nicholls & Cazenave, 2010;Davtalab et al, 2020). Estimations from the Intergovernmental Panel on Climate Change (IPCC) suggest a future increase in Global Mean Sea Level (GMSL) rise.…”
Section: Introductionmentioning
confidence: 99%